Abridgment of Traditional Procurement and E-Procurement: Definitions, Tools and Benefits - Noraizah Abu Bakar; Konrad Peszynski; Veera Pandiyan Kaliani Sundram; Nurdiana Azizan (UiTM Press, 2024)
Vol 4 No 1